Prognostic significance of circulating tumor DNA in urothelial carcinoma patients undergoing immune checkpoint inhibitor therapy: a systematic review and meta-analysis - Ma, Qingping; Hou, Shufu; Ma, Haibo; Gao, Jing; Song, Dandan (Frontiers in Immunology, 2025)
BackgroundCirculating tumor DNA (ctDNA) has emerged as a novel biomarker with the advantages of being non-invasive and enabling dynamic monitoring, providing significant clinical insights into the prognosis and management of malignancies. However, its prognostic role in patients with urothelial carcinoma (UC) receiving immune checkpoint inhibitors (ICI) remains controversial. This study aims to systematically review and perform a meta-analysis to evaluate the prognostic significance of ctDNA levels in this specific patient population.MethodsWe conducted a comprehensive search of the PubMed, Cochrane Library, CNKI, and EMBASE databases to include studies published up to November 14, 2024, assessing the prognostic value of ctDNA in UC patients treated with ICI. Fixed-effects or random-effects models were used to evaluate the association between ctDNA levels and overall survival (OS), progression-free survival (PFS)/disease-free survival (DFS). Funnel plots, Begg’s test, and Egger’s test were employed to assess publication bias.ResultsNine studies from eight articles, comprising a total of 862 urothelial carcinoma (UC) patients treated with immune checkpoint inhibitors (ICIs), were included in this meta-analysis. Seven studies investigated the association between baseline circulating tumor DNA (ctDNA) status and clinical outcomes. Compared to patients without detectable ctDNA, those with elevated baseline ctDNA levels exhibited significantly shorter progression-free survival/disease-free survival (PFS/DFS) (HR = 2.75, 95% CI = 1.36-5.58, P = 0.005), though no statistically significant difference was observed in overall survival (OS) (HR = 2.08, 95% CI = 0.83-5.24, P = 0.119). Additionally, we evaluated the prognostic value of ctDNA dynamics during ICI therapy. A decline or clearance of ctDNA levels was significantly associated with improved clinical outcomes (OS: HR = 0.10, 95% CI = 0.02-0.47, P = 0.004; PFS/DFS: HR = 0.27, 95% CI = 0.16-0.45, P < 0.001).ConclusionsThis meta-analysis demonstrates that detectable ctDNA is significantly associated with PFS or DFS in patients with UC undergoing ICI therapy. Moreover, dynamic changes in ctDNA are strongly correlated with OS and PFS/DFS. Therefore, ctDNA serves as a valuable tool for pre-treatment diagnostic assessment and patient stratification and plays a crucial role in monitoring treatment response and tracking disease progression throughout therapy.Systematic review registrationwww.inplasy.com, identifier INPLASY202520058.